1980
DOI: 10.1063/1.91831
|View full text |Cite
|
Sign up to set email alerts
|

Plastic deformation and fracture resulting from stresses caused by differential thermal contraction in GaP/Si heterostructures

Abstract: Cleavage cracks form in thick (≳5 μm) GaP layers deposited epitaxially on Si during the cooldown after growth. The distribution of stresses caused by differential thermal contraction in such heterostructures has been analyzed, and suggests that stress relief through plastic deformation explains why GaP layers thinner than 5 μm do not crack. Large-area, crack-free layers thicker than 5 μm have been grown on Si-on-sapphire substrates because the resultant stresses in the GaP layers are compressive rather than te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Si/SiGe buffer shows a significant improvement in dark current, photoresponse, and spectral range due to enhanced tensile strain and a better Ge film quality. rameters and theoretical formula in [12] and [13], the tensile strain in Ge after annealing at 600 • C is estimated to be 0.17%, which is close to the values obtained from samples with SiGe buffer. The enhanced tensile strain in Ge using Si/SiGe buffer results in bandgap narrowing, as shown in Fig.…”
Section: Resultssupporting
confidence: 59%
“…Si/SiGe buffer shows a significant improvement in dark current, photoresponse, and spectral range due to enhanced tensile strain and a better Ge film quality. rameters and theoretical formula in [12] and [13], the tensile strain in Ge after annealing at 600 • C is estimated to be 0.17%, which is close to the values obtained from samples with SiGe buffer. The enhanced tensile strain in Ge using Si/SiGe buffer results in bandgap narrowing, as shown in Fig.…”
Section: Resultssupporting
confidence: 59%
“…This strain is accumulated during the reduction of substrate temperature at the end of the growth and is due to the difference between the thermal expansion coefficient of Ge and Si (22). As a consequence, annealed samples exhibit higher levels of tensile strain.…”
Section: Resultsmentioning
confidence: 96%
“…The tensile strain model is mainly considering the direct band gap shrinkage and the absorption coefficient increase. Experimental measurements have confirmed that the epitaxially Ge layer on Si substrate existence a tensile strain, which is generated during the cooling from the high growth temperature due to the thermal‐expansion mismatch between Ge and Si (Tsui and Gershenson, 1980). The strain is dependent on the growth temperature of the Ge film, and 0.34 percent is anticipated the largest value in the case of cooling from the melting point of Ge (937°C) (Sze, 1981).…”
Section: Numerical Analysis Models and Parametersmentioning
confidence: 93%